Role of the labor inspectorate in the management of psycho-sociological occupational risks between control functions and prevention functions - Benaimour, Amina (Journal of Human Sciences, 2023)
The Labour Inspectorate, as a supervisory body, plays a key role in enforcing the laws and regulations relating to health and safety in the employing establishment, in accordance with Article 2 of Act No. 90-03 as amended and completed relating to the labour inspection, in particular its important role in the prevention of psycho-sociological occupational risks affecting workers at the workplace.As a result, Parliament has assigned a number of legal mechanisms to the Commission to exercise its oversight role (including conducting reviews, investigating and reviewing occupational health records), and its preventive role under Act No 88-07 on the protection of occupational health, safety and medicine. This led us to question the effectiveness of labour inspection in the control and prevention of psycho-sociological risks and their prevention in the workplace.